DISCUSSION ISSUES OF ETHNOGRAPHIC RESEARCH OF THE YENISEI KYRGYZ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the main controversial issues in ethnographic studies of the Yenisei Kyrgyz. The study analyzes the main theories and methodological approaches to ethnogenesis, contradictions in historical sources, and the correspondence of ethnographic and archaeological evidence. The theories of the origin of the Kyrgyz - Turkic, autochthonous and mixed - as well as the linguistic and mythological meanings of the ethnonym «Kyrgyz» are studied. Features and contradictions in data from Chinese, Arabic, Persian and Russian sources are discussed. Comparison of archaeological finds and ethnographic data on material and spiritual culture allowed us to get a broad idea of the lifestyle, beliefs and cultural values of the Yenisei Kyrgyz. In conclusion, the article notes the influence of controversial issues encountered in research on the development of science, and suggests new opportunities and challenges for future research. It is emphasized that the ethnography of the Yenisei Kyrgyz is an important source of information for studying the cultural heritage of Turkic and nomadic peoples.
Keywords: Yenisei Kyrgyz, ethnogenesis, ethnography, archeology, historical sources, digital technologies, spiritual culture.